Development of Project-Based Interactive Multimedia for Science to Improve Critical Reasoning in Elementary School Students - Yuni Karsih Asmi; Yuli Prihatni; Ana Fitrotun Nisa; Akbar Al Masjid (Postgraduate, University of Mataram, 2026)
The low critical reasoning ability of elementary school students in science learning requires learning innovations that are able to integrate technology, project activities, and active student involvement. This study aims to develop interactive multimedia science based on projects and test its validity and effectiveness in improving critical reasoning of elementary school students. The type of research used is research and development (R&D) with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Quantitative data were collected through questionnaires, observations and critical reasoning questions, while qualitative data were obtained from suggestions and validators of media and materials. The product was tested on 39 students from two elementary schools in Klaten Regency. The sample in this study was selected using a purposive random sampling technique. Data were analyzed using t-tests and N-gain tests to determine the effectiveness of the product in improving critical reasoning. The results of the study showed that the validation of media and materials each obtained a percentage of 87.92% (feasible) and 93.69% (very feasible), and the results of the t-test showed a probability value of 0.004 < 0.05 which indicated a significant influence on improving students' critical reasoning. The results of the N-gain test also showed an increase in students' critical reasoning after the use of project-based interactive multimedia for science and technology. Therefore, it can be concluded that project-based interactive multimedia for science and technology meets the criteria of feasibility and effectiveness so that it can be applied in science and technology learning in elementary schools.